Clinical approach to vriddhi roga W.S.R to mootravriddhi - Amareshappa; Manoj Kumar; Shailaja S V (International Journal of Pharmacy and Analytical Research, 2022)
Vriddhi indicates pathological increase in dosha & dhatu. Doshavriddhikaraahara -vihara is the main cause for vriddhi. Acharya Susrutha has classified vriddhiroga into 7 types. Vatadosha is the main component in the development of vriddhiroga. In Vriddhiroga Charaka mentioned Virechanadi chikitsa can be adopted in aamavastha of doshajavriddhiroga and Vranachikitsa in Pakvavastha. In case of medovriddhi, kaphajavriddhi, mootravriddhi , Patana, Seevana followed by Vranaropana chikitsa should be adopted. Mootravriddhi is the type vriddhi is caused due to vataprakopa which leads to accumulation of mootra in vrushana. Ambupoornadhrutivat kshoba, Mrudu, Saruk, Mootrakruchcha, Chalayanaphalakosha are the signs and symptoms of mootravriddhi. It can be compared to vaginal hydrocele. The defect in obliteration of the vitello-intestinal duct is the main cause for hydrocele. Clinically it is classified into Congenital and Acquired, congenital hydrocele common at early age of life due to patent Vitello - intestinal duct.The acquired variety type is classified into Vaginal hydrocele, Infantile hydrocelebilocular hydrocele, encysted hydrocele, hydrocele of the hernia sac, hydrocele of the canal of the nuck, the other secondary hydrocele is Post herniorrhaphy hydrocele, Filarial hydrocele, Chylocele. Blood routine, urine routine, USG scrotum, aspiration are the main diagnostic criteria. The differential diagnosis of hydrocele is inguinal hernia, epididymal cyst, spermatocele, testicular tumour, infection, pyocele, haematocele, atropy of testis, infertility, hernia of hydrocele sac. Surgery is the choice of treatment; it includes subtotal excision, jobouleys operation, evacuation & evertion. Even acharyas also mentioned shastra karma for management of mootravriddhi.